Interaction of Depression and Nicotine Addiction on the Severity of Chronic Obstructive Pulmonary Disease: A Prospective Cohort Study - Peian LOU; Peipei CHEN; Pan ZHANG; Jiaxi YU; Yong WANG; Na CHEN; Lei ZHANG; Hongmin WU; Jing ZHAO (Tehran University of Medical Sciences, 2016)
Background: Depression and smoking decrease health status in Chronic Obstructive Pulmonary Disease (COPD), but the combined effect of the two factors is unknown. This study aimed to assess the interactive effects of depression and smoking on the severity of patients with COPD. Methods: A prospective cohort study including 2,268 patients with COPD was conducted in seven rural communities from May 2008 to May 2012. The relationships between the BODE (body mass index, airflow obstruction, dyspnea, and exercise capacity) index and depression and nicotine addiction were assessed. The product of depression and smoking was added to the logistic regression model to evaluate the multiplicative interaction and relative excess risk of interaction (RERI). The Attributable Proportion (AP) of interaction and the synergy index (S) was applied to evaluate the additive interaction of two factors. Results: The severity of COPD in patients with depressive symptoms who never smoked was increased 1.74-fold and in smoking patients it increased by 6.08-fold. Highly addicted smokers with depressive symptoms had a nearly 40-fold increase in severity (all P<0.001). The increased values of the BODE index, HADS-D and Fagerström score also correlated positively (P<0.001). The co-presence of depressive symptoms and smoking significantly increased the BODE index by 11.99-fold with significant biological interactions, relative excess risk of interaction (RERI) was 12.12, the biological interactions were increased with increasing nicotine addiction. Conclusions: Patients with depressive symptoms who also smoke have an increased risk of severity from COPD interaction effects. The risk for severity of COPD and depressive symptoms increased with increasing the severity of nicotine addiction.